A note on Medieval Mediterranean trade networks: first observations on the possible evidence of Sicilian amphorae of the 8th-9th century in Crete and the Aegean - Randazzo, Matteo G. (Journal of Greek Archaeology, 2022)
Nearly a quarter of a century has gone by since scholars working on the Medieval Mediterranean were wondering if Byzantium was dead or alive during the 8th-9th centuries. Indeed, until recently, it was still quite a prevailing view that this period marked the ‘Dark Ages’ for the Byzantine Empire, in all the facets of its administrative, economic, and sociocultural life. Scholarly debate of the last years has zealously challenged this view, depicting a smoother and less pessimistic picture of this period. For instance, leaving aside historical and artistic aspects, and focusing on the theme of this report – that is Medieval amphorae – already in the mid-2010s it was clear that the Mediterranean remained a dynamic economic system throughout the 8th-9th century. This argument, which was mostly drawn on the evidence of the so-called Aegean globular amphorae, was further embodied and enhanced in 2018, during a thematic conference of the AIECM3 group, which was entirely dedicated to Medieval Mediterranean amphorae from the 8th to 12th centuries. Among the main and most valuable contributions, Cacciaguerra’s article shed light on the Mediterranean patterns of distribution of a specific type of amphora of the 8th-9th century produced in Sicily. Back then, amphorae of this kind were known outside Sicily, mostly along the Adriatic, but were utterly unknown eastward of the Otranto Straight. The aim of this short report is twofold: 1. to elaborate on this mainstream study-theme of Medieval Mediterranean amphorae and trade networks; 2. to expand on the current record of extra-regional evidence of Sicilian amphorae of the 8th-9th century by discussing the evidence of possible specimens documented in Crete and into the Aegean.